A case-control study of urinary concentrations of bisphenol A, bisphenol F, and bisphenol S and the risk of papillary thyroid cancer. (January 2023) - Zhang, Lei; Zhang, Jiahuai; Fan, Sai; Zhong, Yuxin; Li, Jingguang; Zhao, Yunfeng; Ni, Song; Liu, Jiaying; Wu, Yongning
Abstract: The incidence of thyroid cancer (TC), especially papillary thyroid cancer (PTC), has dramatically increased globally. Whereas some endocrine disruptors have been linked to neoplastic processes, the associations between human exposure to bisphenol analogs and the risk of TC remain unclear. This present case-control study examined the associations between the urinary concentrations of bisphenol A (BPA) and other bisphenols, namely bisphenol F (BPF) and bisphenol S (BPS), and the risk of PTC. After adjusting for confounders and creatinine standardization, significantly positive associations were observed for BPF (odds ratio [OR] = 1.80, 95% confidence interval [CI] = 1.27–2.54), but negative associations observed for BPA (OR = 0.38, 95% CI = 0.19–0.77) and BPS (OR = 0.63, 95% CI = 0.43–0.93), in the total population. However, after stratification by age and smoking, statistical significance was retained only in non-smoking women, suggesting the adverse effects of BPF exposure on PTC risk, especially in women. These findings require replication and confirmation in further research. Graphical abstract: Image 1 Highlights: Associations of bisphenols exposure with PTC risk examined in a case-control study. Higher levels of BPF, but not BPA and BPS, were observed in PTC patients. Significant associations observed only in female non-smokers. Nonmonotonic relationships between BPF exposure and PTC risk were observed.